Comparison of adequacy between transbronchial lung cryobiopsy samples and endobronchial ultrasound‐guided transbronchial needle aspiration samples for next‐generation sequencing analysis. Issue 2 (3rd December 2020) - Tone, Mari; Inomata, Minoru; Awano, Nobuyasu; Kuse, Naoyuki; Takada, Kohei; Minami, Jonsu; Muto, Yutaka; Fujimoto, Kazushi; Kumasaka, Toshio; Izumo, Takehiro
Abstract: Background: Most lung cancer patients present with lesions in both lung fields and lymphadenopathy. Thus, transbronchial lung cryobiopsy (TBLC) and endobronchial ultrasound‐guided transbronchial needle aspiration (EBUS‐TBNA) are commonly performed for diagnosing lung cancer. However, the adequacy of these samples for next‐generation sequencing (NGS) analysis remains unclear. This study aimed to compare the adequacy between TBLC and EBUS‐TBNA samples for NGS analysis. Methods: This retrospective cohort study included patients whose lung samples were collected via TBLC or EBUS‐TBNA and analyzed using NGS. Out of 46 genes, the number of genes in TBNA and TBLC samples that could not be assessed via NGS analysis was mainly evaluated. Results: A total of 37 patients were included and classified into two groups (TBLC group, n = 18 and TBNA group, n = 19). The mean number of genes that could not be evaluated via NGS analysis was significantly lower in the TBLC group than in the TBNA group (0.9 vs. 10.3, P = 0.024). The median total area of tumor cells in TBLC samples was significantly greater than that in TBNA samples (6.3 [1.6–4.2] vs . 2.6 [0.2–17.3] mm 2, P  < 0.01). In the TBNA group, there were two fully inadequate samples for NGS analysis with a high degree of cell crush or low tumor content, while there was no fully inadequate sample in the TBLC group. Conclusions: TBLC is more effective in obtaining adequate samples for NGS analysis than EBUS‐TBNA. TBLC should be performed to obtain adequate samples for NGS analysis in lung cancer patients with target lesions in lung fields, even if they have lymphadenopathy. Key points: Significant findings of the study The mean number of genes that could not be evaluated was significantly lower in TBLC samples than in EBUS‐TBNA samples (0.9 vs. 10.3, P = 0.024). TBLC could obtain adequate samples with a high concentration of uncrushed tumor cells for NGS. What this study adds To obtain samples for NGS analysis, the use of TBLC should be aggressively considered in lung‐cancer patients with target lesions located in lung fields, even if they have lymphadenopathy. Abstract : The adequacy for next generation sequencing (NGS) in transbronchial lung cryobiopsy (TBLC) and endobronchial ultrasound‐guided transbronchial needle aspiration (EBUS‐TBNA) samples remains unclear. We found the mean number of genes which could not be assessed via NGS was significantly lower in TBLC samples than EBUS‐TBNA samples. TBLC could obtain adequate samples with a high concentration of uncrushed tumor cells for NGS.